81st EAGE Conference and Exhibition 2019 2019
DOI: 10.3997/2214-4609.201900844
|View full text |Cite
|
Sign up to set email alerts
|

Using Convolutional Neural Networks for Denoising and Deblending of Marine Seismic Data

Abstract: Processing marine seismic data is computationally demanding and consists of multiple timeconsuming steps. Neural network based processing can, in theory, significantly reduce processing time and has the potential to change the way seismic processing is done. In this paper we are using deep convolutional neural networks (CNNs) to remove seismic interference noise and to deblend seismic data. To train such networks, a significant amount of computational memory is needed since a single shot gather consists of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…In the training process with the GT method (Figure 1), the training data pair is selected as false{s,bolds1false}$\{ {{\bf s},{{\bf s}}_1} \}$ (Richardson & Feller, 2019; Slang et al., 2019; Sun et al., 2020; Zu et al., 2020). The network parameter trained by this training data set is θA${{\bm{\theta }}}^A$.…”
Section: Methodsmentioning
confidence: 99%
“…In the training process with the GT method (Figure 1), the training data pair is selected as false{s,bolds1false}$\{ {{\bf s},{{\bf s}}_1} \}$ (Richardson & Feller, 2019; Slang et al., 2019; Sun et al., 2020; Zu et al., 2020). The network parameter trained by this training data set is θA${{\bm{\theta }}}^A$.…”
Section: Methodsmentioning
confidence: 99%
“…However, we note that once the network is trained, the actual denoising of a single shot gather is done in less than a second. The results obtained using a NDCNN were quite encouraging, but the network performed less optimal in cases with a low SNR (Slang et al 2019). In order to reduce the training time and possibly improve the denoising results further, a second class of CNN network architectures was investigated, namely the U-Net (Ronneberger et al 2015).…”
Section: A C U S T O M I Z E D U -N E T F O R a T T E N U A T I O N Omentioning
confidence: 99%
“…Slang et al . () employed marine seismic field data and demonstrated successful applications within deblending and denoising using CNNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many geophysical processes incorporate deep learning tools, which provide more robust solutions than conventional approaches. In data processing: Ovcharenko et al (2019) extrapolated low frequencies from high ones using deep learning; Slang et al (2019) used deep learning for denoising and deblending. For time-lapse processing: Alali et al (2020a) correct for the time shift in the data using a fully-connected layer in the latent space of an autoencoder; Duan et al (2020) showed that a trained network can outperform a conventional cross-correlation method in estimating the time-shift; Alali et al (2020b) suggested to use recurrent neural networks to better account for time dependency in the data.…”
Section: Introductionmentioning
confidence: 99%